Polysaccharide arabinogalactan from larch Larix sibirica as carrier for molecules of salicylic and acetylsalicylic acid: preparation, physicochemical and pharmacological study. (May 2015) - Chistyachenko, Yulia S.; Dushkin, Alexandr V.; Polyakov, Nikolay E.; Khvostov, Mikhail V.; Tolstikova, Tatyana G.; Tolstikov, Genrikh A.; Lyakhov, Nikolay Z.
Abstract Inclusion complexes of salicylic acid (SA) and acetylsalicylic acid (aspirin, ASA) with polysaccharide arabinogalactan (AG) from larch wood Larix sibirica and Larix gmelinii were synthesized using mechanochemical technology. In the present study, we have investigated physicochemical properties of the synthesized complexes in solid state and in aqueous solutions as well as their anti-aggregation and ulcerogenic activity. The evidence of the complexes formation was obtained by nuclear magnetic resonance (NMR) relaxation technique. It was shown that in aqueous solution the molecules of SA and ASA are in fast exchange between the complex with AG macromolecules and solution. The stability constant of aspirin complex was calculated. It was shown that mechanochemically synthesized complexes are more stable when compared to the complex obtained by mixing solutions of the components. Complexes of ASA show two-fold increase of anti-platelet effect. It allows to reduce the dose of the antithrombotic drug and its ulcerogenic activity. These results substantiate the possibility to design new preparations on the basis of ASA with increased activity and safety.